Female Masculinity Portrayal in Dota 2 Videogame - Hanief Filza Ferdiansyah; Muhammad Taufiq Al Makmun (Universitas Sebelas Maret, 2020)
The article aims to explore the female masculinity in Dota 2 female heroes. This research is descriptive qualitative research which focuses to gain deeper understanding about the topic of the research. The topic of this research is female masculinity in Dota 2 videogame. By applying semiotic theory of Roland Barthes, this research analyzes the appearance, particularly the costume of the female heroes in Dota 2 to find the presentation of female heroes in Dota 2. Then, the female masculinity theory of Judith Halberstam categorizing female masculinity into five categories utilizes to find the masculinity of female heroes in the videogame. This research uses socio-cultural approach in accordance to find the context of American society in 2010s. Therefore, this research finds that there is female masculinity manifestation in the female heroes of Dota 2. Thus, the female masculinity manifested in the Dota 2 female heroes shares values from the fourth wave feminism that happens in United States in the era of 2010s.Keywords: feminism, videogame, new media, female masculinity, American studies